HUBUNGAN AKTIVITAS FISIK DAN DIET TERHADAP KADAR GULA DARAH PADA PENDERITA DIABETES MELLITUS TIPE-II DI RSUD MEURAXA KOTA BANDA ACEH - Cut Ana Martafari; Julinar Julinar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Type 2 diabetes mellitus is a hyperglycemic disease due to insulin sensitivity. Type 2 diabetes mellitus is caused by irreversible risk factors such as gender, age, and genetic factors. In addition, risk factors are thought to cause an increased incidence of type 2 diabetes mellitus due to lack of physical activity and an increase in body weight in a person. This type of research is observational analytic research with cross sectional design. The purpose of this study was to determine the relationship between physical activity and diet on blood sugar levels in patients with type 2 diabetes mellitus in Meuraxa District Hospital, Banda Aceh. The results of the study with p-value = 0.001 there is a relationship between physical activity and blood glucose levels, because the habit of physical activity and exercise will increase glucose absorption for muscle formation, and can improve insulin sensitivity so that high blood glucose can be controlled. In addition, there is also a relationship between dietary patterns on blood sugar levels in patients with type 2 diabetes mellitus in hospitals Meuraxa with p-value= 0.014.Keywords: Type 2 diabetes mellitus sufferers, glucose levels, physical activity and diet